Efficacy of alginate- and clay-encapsulated microorganisms on the growth of araçá-boi seedlings (Eugenia stipitata) - Nascimento, Fernanda Cristina [UNESP] (2019)
The present work aimed to evaluate the effects of encapsulated microorganisms on seedlings of Eugenia stipitata, popularly known as araçá-boi, to evaluate the interaction between the inoculum and encapsulating agents such as clay and alginate. The experiment was carried out in a completely randomized design using a 3×2 factorial scheme. The treatments were control, inoculum, clay without microbial inoculum, clay with microbial inoculum, alginate without microbial inoculum, and alginate with microbial inoculum. The seedlings were grown under nursery conditions over a period of 3 months. No treatment increased the height, stem diameter, shoot dry matter or root dry matter of the araçá-boi seedlings. The use of alginate increased the ammonium content compared to the clay and control treatments. Alginate and clay increased the nitrate content in relation to the control. Alginate increased the total number of bacteria in relation to the clay and control treatments. The application of inoculum combined with alginate increased the nitrate content only in relation to the clay and control treatments. Although the application of inoculum promoted an increase in the nitrate content compared to the uninoculated treatments, there was no effect for the other parameters analyzed. The results suggest that clay and alginate encapsulating agents with the presence or absence of microorganisms may improve some soil parameters.